Immunotherapy with methyl gallate, an inhibitor of Treg cell migration, enhances the anti-cancer effect of cisplatin therapy - Kim, Hyunseong; Lee, Gihyun; Sohn, Sung-Hwa; Lee, Chanju; Kwak, Jung Won; Bae, Hyunsu (The Korean journal of physiology & pharmacology, 2016)
Foxp3(+) CD25(+)CD4(+) regulatory T (Treg) cells are crucial for the maintenance of immunological self-tolerance and are abundant in tumors. Most of these cells are chemo-attracted to tumor tissues and suppress anti-tumor responses inside the tumor. Currently, several cancer immunotherapies targeting Treg cells are being clinically tested. Cisplatin is one of the most potent chemotherapy drugs widely used for cancer treatment. While cisplatin is a powerful drug for the treatment of multiple cancers, there are obstacles that limit its use, such as renal dysfunction and the development of cisplatin-resistant cancer cells after its use. To minimize these barriers, combinatorial therapies of cisplatin with other drugs have been developed and have proven to be more effective to treat cancer. In the present study, we evaluated the eff ect of the combination therapy using methyl gallate with cisplatin in EL4 murine lymphoma bearing C57BL/6 mice. The combinatorial therapy of methyl gallate and cisplatin showed stronger anti-cancer eff ects than methyl gallate or cisplatin as single treatments. In Treg cell-depleted mice, however, the eff ect of methyl gallate vanished. It was found that methyl gallate treatment inhibited Treg cell migration into the tumor regardless of cisplatin treatment. Additionally, in both the normal and cisplatin-treated tumor-bearing mice, there was no renal toxicity attributed to methyl gallate treatment. These findings suggest that methyl gallate treatment could be useful as an adjuvant method accompanied with cisplatin therapy.